Does Work Engagement Effectively Predict Subjective Well-Being? : A Meta-Analysis Using R Statistical Software - Ding, Hui; Si, Shoujing (Applied mathematics and nonlinear sciences, 2023)
Does work engagement effectively predict subjective well-being? In this paper, we investigated the relationship between work engagement and subjective well-being by synthesizing 176 effects from 59 studies involving 21927 subjects. The results showed that work engagement were positively correlated with subjective well-being, while job burnout were negatively correlated with subjective well-being. Literature sources significantly adjusted the relationship among work engagement, job burnout and subjective well-being. The paper proved that work engagement and subjective well-being are closely related, and literature sources may play a moderating role.